Development of microsatellite, gene-specific and species-specific markers for hybrid detection of plants in Jatropha genus - Changjalern, Matiya; Srinophakun, Penjit; Hongtrakul, Vipa (Agriculture and Natural Resources, 2023)
Importance of the work: Jatropha curcas has been identified as a potential biodiesel source. It has a narrow genetic base and lacks cultivars with a high seed yield and oil content. Therefore, interspecific hybridization and hybridity testing are important for its genetic improvement. Objectives: To develop three specific DNA markers and to test their efficiency for hybrid detection of plants in the genus Jatropha. Materials & Methods: Microsatellite, gene-specific and species-specific markers were developed and used to confirm hybrids from interspecific hybridization for the crosses J. curcas × J. integerrima, J. curcas × J. multifida and J. curcas × J. podagrica. Results: In total, 22 microsatellite primer pairs, 18 single strand conformational polymorphism primer pairs specific to 11 genes and 25 species-specific primer pairs were designed and used to verify interspecific hybrids. All three types of DNA markers developed were effective for the identification of hybrids from interspecific hybridization. Main finding: The development of the three specific DNA markers for plants in the genus Jatropha provided useful information for genetic analysis, hybrid selection and the development of biodiesel plant breeding.